IFI16 Preferentially Binds to DNA with Quadruplex Structure and Enhances DNA Quadruplex Formation - Hároníková, Lucia; Coufal, Jan; Kejnovská, Iva; Jagelská, Eva B; Fojta, Miroslav; Dvořáková, Petra; Muller, Petr; Vojtesek, Borivoj; Brázda, Václav (PloS one, 2016)
Interferon-inducible protein 16 (IFI16) is a member of the HIN-200 protein family, containing two HIN domains and one PYRIN domain. IFI16 acts as a sensor of viral and bacterial DNA and is important for innate immune responses. IFI16 binds DNA and binding has been described to be DNA length-dependent, but a preference for supercoiled DNA has also been demonstrated. Here we report a specific preference of IFI16 for binding to quadruplex DNA compared to other DNA structures. IFI16 binds to quadruplex DNA with significantly higher affinity than to the same sequence in double stranded DNA. By circular dichroism (CD) spectroscopy we also demonstrated the ability of IFI16 to stabilize quadruplex structures with quadruplex-forming oligonucleotides derived from human telomere (HTEL) sequences and the MYC promotor. A novel H/D exchange mass spectrometry approach was developed to assess protein interactions with quadruplex DNA. Quadruplex DNA changed the IFI16 deuteration profile in parts of the PYRIN domain (aa 0-80) and in structurally identical parts of both HIN domains (aa 271-302 and aa 586-617) compared to single stranded or double stranded DNAs, supporting the preferential affinity of IFI16 for structured DNA. Our results reveal the importance of quadruplex DNA structure in IFI16 binding and improve our understanding of how IFI16 senses DNA. IFI16 selectivity for quadruplex structure provides a mechanistic framework for IFI16 in immunity and cellular processes including DNA damage responses and cell proliferation.
Keywords: jaderné proteiny; Nuclear Proteins; G-Quadruplexes; Humans; DNA; Nucleic Acid Conformation; Phosphoproteins; Response Elements; Protein Binding; vazba proteinů; konformace proteinů; responzivní elementy; Protein Conformation; G-kvadruplexy; lidé; konformace nukleové kyseliny; fosfoproteiny